Flexible Thermal Sensitivity of Mitochondrial Oxygen Consumption and Substrate Oxidation in Flying Insect Species - Menail, Hichem A.; Cormier, Simon B.; Ben Youssef, Mariem; Jørgensen, Lisa Bjerregaard; Vickruck, Jess L.; Morin, Pier; Boudreau, Luc H.; Pichaud, Nicolas (Frontiers in Physiology, 2022)
Mitochondria have been suggested to be paramount for temperature adaptation in insects. Considering the large range of environments colonized by this taxon, we hypothesized that species surviving large temperature changes would be those with the most flexible mitochondria. We thus investigated the responses of mitochondrial oxidative phosphorylation (OXPHOS) to temperature in three flying insects: the honeybee (Apis mellifera carnica), the fruit fly (Drosophila melanogaster) and the Colorado potato beetle (Leptinotarsa decemlineata). Specifically, we measured oxygen consumption in permeabilized flight muscles of these species at 6, 12, 18, 24, 30, 36, 42 and 45°C, sequentially using complex I substrates, proline, succinate, and glycerol-3-phosphate (G3P). Complex I respiration rates (CI-OXPHOS) were very sensitive to temperature in honeybees and fruit flies with high oxygen consumption at mid-range temperatures but a sharp decline at high temperatures. Proline oxidation triggers a major increase in respiration only in potato beetles, following the same pattern as CI-OXPHOS for honeybees and fruit flies. Moreover, both succinate and G3P oxidation allowed an important increase in respiration at high temperatures in honeybees and fruit flies (and to a lesser extent in potato beetles). However, when reaching 45°C, this G3P-induced respiration rate dropped dramatically in fruit flies. These results demonstrate that mitochondrial functions are more resilient to temperatures in honeybees compared to fruit flies. They also indicate an important but species-specific mitochondrial flexibility for substrate oxidation to sustain high oxygen consumption levels at high temperatures and suggest previously unknown adaptive mechanisms of flying insects’ mitochondria to temperature.